EFL Preservice Teacher Perception Toward The Use of Mobile Assisted Language Learning (MALL) in Teaching English - Asma Rozak Nada Yuniar; Putu Dian Danayanti Degeng (South Sulawesi Education Development (SSED), 2025)
Mobile-Assisted Language Learning (MALL) has developed as a promising approach in English language education, offering flexibility, accessibility, and enhanced digital engagement. This study seeks to investigate preservice teachers’ perceptions toward MALL during their teaching practice through a quantitative research method. A Likert-scale questionnaire was administered to 112 preservice teachers at Universitas Brawijaya to assess their views on the usefulness of MALL in English instruction. The results reveal that preservice teachers generally hold positive attitudes toward the integration of MALL. Approximately 96% of respondents agreed that MALL enhances task efficiency, and 95% believed it contributes to improved teaching outcomes. The highest-rated item indicated that MALL is particularly helpful in completing instructional tasks. However, the lowest-rated item, though still positive, reflected some uncertainty about MALL’s impact on more complex aspects of teaching. Despite these minor concerns, 91% of participants expressed a willingness to integrate MALL into their future classrooms. These findings suggest that MALL is widely viewed as an effective instructional tool that aligns with modern educational goals. Based on the results, the study recommends incorporating more MALL-focused training within teacher education programs to better equip preservice teachers for the demands of digital instruction. Keywords: Mobile-assisted Language Learning (MALL), Perceptions, Preservice English Teachers, Mobile Devices